A review of macroalgae production, with potential applications in biofuels and bioenergy. (February 2016) - Ghadiryanfar, Mohsen; Rosentrater, Kurt A.; Keyhani, Alireza; Omid, Mahmoud
Abstract: This review discusses biofuel and bioenergy production from seaweed, and ranges from cultivation to final product, and investigates opportunities, problems, advantages, disadvantages and other issues of this emerging industry. High levels of structural polysaccharides and low lignin contents make seaweed attractive feedstocks for production of liquid biofuels via fermentation and biogas production via anaerobic digestion. Since macroalgae can be grown in water (oceans and lakes), they will not compete with land-based crops, and thus will not be in competition with human foods. And biofuel and bioenergy production from macroalgae has some environmental benefits. Electricity produced from biogas derived from macroalgae can be cost-competitive to solar thermal, solar photovoltaic and biomass generated electricity. Biofuel and bioenergy production from macroalgae, however, will entail higher costs than terrestrial biomass feedstocks due to higher costs of cultivation and higher costs to remove harmful content such as sulfur and nitrogen from the resulting fuel or heavy metals from the residues. Economic production of biofuels and bioenergy will be available by increasing the scale and efficiency of production of this emerging resource.